Streptococcus pneumoniae Serotype 12F-CC4846 and Invasive Pneumococcal Disease after Introduction of 13-Valent Pneumococcal Conjugate Vaccine, Japan, 2015–2017 - Satoshi Nakano; Takao Fujisawa; Yutaka Ito; Bin Chang; Yasufumi Matsumura; Masaki Yamamoto; Shigeru Suga; Makoto Ohnishi; Miki Nagao (Emerging Infectious Diseases, 2020)
To prevent invasive pneumococcal disease (IPD), pneumococcal conjugate vaccines (PCVs) have been implemented in many countries; however, many cases of IPD still occur and can be attributable to nonvaccine serotypes of Streptococcus pneumoniae. In Japan, the number of IPD cases attributable to serotype 12F increased from 4.4% in 2015 to 24.6% in 2017 after 13-valent PCV was introduced. To clarify the associated genetic characteristics, we conducted whole-genome sequencing of 75 serotype 12F isolates. We identified 2 sequence types (STs) among the isolates: ST4846, which was the major type, and ST6945. Bayesian analysis suggested that these types diverged in »1942. Among serotype 12F-ST4846, we identified a major cluster, PC-JP12F, whose time of most recent common ancestor was estimated to be »2012. A phylogeographic analysis demonstrated that PC-JP12F isolates spread from the Kanto region, the most populated region in Japan, to other local regions.